166k views
5 votes
Eliminate the parameter.

x = one divided by two t, y = 3t^3 - 1

Answer choices:
y = three divided by eight t^3 - 1
y = 24x^3 - 1
y = 6x^3 - 1
y = 24x - 1

2 Answers

0 votes
x = one divided by two t
x = 1/2t; t = 2x

Substitute the t in the equation:
y = 3t^3 - 1
y = 3(2x)^3 - 1
y = 3(8x^3) - 1
y = 24x^3 - 1


The answer is y = 24x^3 - 1

Hope this helps! Goodluck
User Greg Mason
by
5.7k points
4 votes
Answer:
y = 24x³ - 1

Step-by-step explanation:
We have:
x =
(1)/(2) t
This means that:
t = 2x ...............> I

We are also given that:
y = 3t³ - 1 .............> II

Substitute with I in II to eliminate the t as follows:
y = 3t³ - 1
y = 3*(2x)³ - 1
y = 3*8x³ - 1
y = 24x³ - 1

Hope this helps :)

User Yuriy Tseretyan
by
6.1k points